Kramer’s scale or transcutaneous bilirubinometry: the ideal choice of a pediatrician? can we trust our eyes? - Varughese, Pearl Mary (International Journal of Contemporary Pediatrics, 2019)
Background: Neonatal hyperbilirubinemia, though benign in 80% cases, can lead to kernicterus if not diagnosed and treated early. The golden method of estimation is measuring serum bilirubin levels. Both Kramer’s scale and Transcutaneous bilirubinometer are non -invasive methods. Its high time the pediatricians choose an ideal non-invasive and reliable method to detect hyperbilirubinemia. Objective of this study is to find out which has a better correlation with serum bilirubin - transcutaneous bilirubinometer reading (TcB) or Kramer's scale. Methods: The study was conducted in a tertiary newborn center from November 2014 to June 2016. The inclusion criteria included all babies above 34 weeks gestation and exclusion criteria included babies with established direct hyperbilirubinemia, neonatal septicemia, major congenital/ gastrointestinal malformations and those on phototherapy. The sample size was 450 and the correlation was analyzed using ROC curves and plots of agreement was done using Bland Altman charts. Results: The incidence of significant Hyperbilirubinemia is 12%. Transcutaneous bilirubin level had a better correlation and prediction level compared to Kramer at both 24 hours and 48 hours. Bland Altman analysis showed that transcutaneous values were closer to the total serum bilirubin level compared to Kramer values. Conclusion: Transcutaneous bilirubinometry is a better and more ideal choice to replace serum bilirubin levels. In settings where TcB is not feasible, it’s always best to screen for jaundice using Kramer’s scale rather than estimating serum bilirubin values in all babies. In babies where TcB levels are above the cut off range, it’s better to do serum bilirubin levels.